MEDICAMENTOS E OUTRAS SUBSTÂNCIAS DURANTE A AMAMENTAÇÃO: CONHECIMENTO DE LACTANTES E PROFISSIONAIS DE SAÚDE E DESCRIÇÃO DO DESENVOLVIMENTO DE UM WEBSITE - Silva, Narllyanna Farias Lira da (2024)
Breastfeeding is essential to children's health. Medication delivery during pregnancy requires special attention to the impact of the milk quality on the child's health. The theme is part of the actions of the National Program of Promotion, Protection, and Support to Breastfeeding and is aligned of the objectives of Sustainable Development related of eradication poverty, health and well-being in addition to zero hunger. Aim: identify the breastfeeding knowledge and health professionals about the use the medications and other substances during breastfeeding, and describe the development and evaluation of the website from the perspective of informing breastfeeding mothers, and health professionals about the use of medications and substances during the breastfeeding. Methodology path: this is a methodological and exploratory-descriptive study including breastfeeding and health professionals. Data collection was acquired by using an online application of two questionnaires about the use of medications and other substances. One of the used is related to health professionals, and the other to breastfeeds. The questionnaires were elaborated based on the risk, according to the Handbook of Health Security. For the analysis of the information, an ANOVA and post-hoc Tukey's test was applied to the independent samples. During the website development, Scrum was used for the management and development of software, communication, and alignment of the project, logotype, layout, and design. The website content was based on the "Breastfeeding and Use of Medication and Other Substances" manual, organized by the Brazilian Department of Health. The website evaluation was performed by using the Validity Index of Contents (IVC in Portuguese), and the percentage of agreements of the evaluations. Results: 81 breastfeeding and 66 health professionals participated in the study. Regarding questions about knowledge, breastfeeding women had a higher frequency of correct answers about the use of substances such as cocaine and crack, but lower performance to medications, with Citalopram. Health professionals obtained a higher frequency of correct answers regarding medications such as paracetamol but presented gaps about the use of psychotropic medications and other substances for breastfeeding women. The website was developed by a multidisciplinary team, using Scrum, and is called “Amamos”. When evaluating the website, an agreement percentage of 98.68% and an IVC of 0.91 were found. Final Consideration: although the high frequency of correct answers in the use of medications is positive, it is essential to improve the training of health professionals and provide clear guidance to breastfeeding women, to avoid inappropriate practices and promote maternal and child health. The website was evaluated with results superior to those recommended, standing out for its easy navigation and understanding, contributing to the health learning process. Furthermore, the study highlights the importance of accessible, reliable, and standardized information to promote safe breastfeeding, in line with public health priorities.